(untitled) (The Research of Medical Science Review, 2025)
Background: Accurate diagnosis of pancreatic lesions is essential for determining appropriate treatment strategies. Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) and computed tomography-guided biopsy (CT-guided biopsy) are commonly used methods for obtaining tissue samples. Objective: To compare the diagnostic outcomes of EUS-FNA and CT-guided biopsy in the evaluation of pancreatic lesions, focusing on diagnostic accuracy, sample adequacy, complication rates, and the need for repeat biopsy. Methods: This prospective observational study was conducted at Multiple Teaching Hospitals of Pakistan during January 2024 till November 2024. A total of 85 patients with suspected pancreatic lesions, referred for tissue diagnosis, were included in the study. EUS-FNA was performed using a linear-array echoendoscope under conscious sedation or general anesthesia, depending on patient tolerance. Results: EUS-FNA demonstrated higher diagnostic accuracy (90.6%) compared to CT- guided biopsy (82.5%). Sample adequacy was significantly better with EUS-FNA (93.3% vs. 82.5%, p = 0.04), reducing the need for repeat biopsy (6.7% vs. 17.5%, p = 0.03). The complication rate was lower in the EUS-FNA group (11.1%) than in the CT-guided biopsy group (20.0%), though this difference was not statistically significant (p = 0.21). Conclusion: It is concluded that EUS- FNA is a superior diagnostic modality for pancreatic lesions, providing higher diagnostic accuracy, better sample adequacy, and lower repeat biopsy rates compared to CT-guided biopsy. CT-guided biopsy remains a useful alternative when endoscopic access is not feasible.